V.2 - Waldrep, Christopher (New York, 2003)
The Civil War shook America to the core of its constitutional foundations. Before the war, the Constitution protected slavery and kept power decentralized. During the Civil War, President Abraham Lincoln gathered enormous national power to combat what he called the (S0(Banarchy(S1 (Bof secession. After the war, the nation struggled to understand what had happened. Historians Christopher Waldrep and Lynne Curry have assembled a collection of constitutional documents to explore the meaning of the Civil War, the influence of constitutionalism on presidential war powers, and the U.S. Supreme Court$1 (Bs fight to limit the war$1 (Bs impact in post-Civil War America.s
Keywords: Constitutional history-United stated